Boya education in China: Lessons from liberal arts education in the U.S. and Hong Kong. (July 2021) - Cheng, Leonard K.; Wei, Xiangdong
Abstract: In this paper, taking as our point of departure the importance of China's " boya " education (BYE) and the West's liberal arts education (LAE) in an era that will be increasingly dominated by information technology (IT) and Artificial Intelligence (AI), we examine the importance of BYE in Mainland China and LAE in the U.S. and Hong Kong. We argue that (a) the recent resurgence and growing significance of LAE in the world has been due to the right skill sets it provides in the information technology era in which many new jobs will be created and existing jobs destroyed ; (b) professional or technical training is not only compatible with the fundamental values of boya or liberal arts but also important in showcasing the strengths of BYE and LAE; (c) the combined benefits of BYE or LAE and professional or technical training may be achieved by adopting the main features of LAE such as its broad-based curriculum and whole-person development approach to undergraduate education or by combining a student's undergraduate and postgraduate studies over time; and (d) for BYE to achieve its goals in China it should occupy a central rather than tangential role in the undergraduate curriculum.